Bioactive compounds and antioxidant activity in various citrus peels: a significant systematic review - Hazrulrizawati, Abd Hamid; Wan Fatimah, Wan Mohd Nowalid; Iwansyah, Ade Chandra; Giwa, Shehu Hadiza (Semarak Ilmu Publishing, 2026)
Citrus peels, traditionally considered byproducts in fruit processing, have garnered increasing attention due to their bioactive compounds and antioxidant characteristics. This systematic literature review aims to comprehensively evaluate and consolidate existing research on the bioactive compounds and antioxidant properties found in various citrus peel varieties. Citrus fruits, particularly their peels, have emerged as substantial repositories of bioactive compounds, including flavonoids, phenolics, and essential oils. Nevertheless, the fragmented nature of existing research on various citrus species, cultivars, and extraction methods underscores the need for a systematic approach. This is essential to provide a cohesive understanding of the inherent bioactive profiles and antioxidant capabilities present within these peels. Employing the Pre-Recording Systematic Reviews and Meta-Analysis (PRISMA) approach, this study executed a systematic search using academic strategies on Scopus and Web of Science databases to identify and select pertinent studies. Advanced search strategies utilizing keywords (1) citrus peel and (2) antioxidant was employed. A rigorous evaluation of methodological and analytical procedures was undertaken, and data were systematically collected for analysis, resulting in a final dataset of studies. This systematic review covered three key themes: (1) Citrus Fruit and Peel Utilization for Health and Nutrition, (2) Anticancer Properties and Chemical Composition of Citrus Products, and (3) Citrus By-Products and Waste Utilization. The review reveals substantial variability in bioactive compounds and antioxidant activities across different citrus peels. This review offers a comprehensive examination of each study's methodology and findings. Ultimately, the findings emphasize the importance of citrus peels as abundant sources of bioactive compounds and antioxidants, with far-reaching implications for nutrition, health, and biotechnological applications. While providing a comprehensive overview of the diverse bioactive profiles in different citrus peels, this review also advocates for further research to unlock their full potential and encourage sustainable practices in the food industry.